2014
DOI: 10.4049/jimmunol.1400725
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Derived α-Fetoprotein Impairs the Differentiation and T Cell Stimulatory Activity of Human Dendritic Cells

Abstract: Several tumor-derived factors have been implicated in DC dysfunction in cancer patients. Alpha-fetoprotein (AFP) is an oncofetal antigen that is highly expressed in abnormalities of prenatal development and several epithelial cancers, including hepatocellular carcinoma (HCC). In HCC patients exhibiting high levels of serum AFP, we have observed a lower ratio of myeloid-to-plasmacytoid circulating DC compared to patients with low serum AFP levels and healthy donors. To test the effect of AFP on DC differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 41 publications
0
83
0
1
Order By: Relevance
“…A series of studies have proposed that AFP is able to regulate other immune cells. Tumor-derived AFP causes suppression of T lymphocyte responses (44). Here, we intended to understand the effect of fetus-derived AFP on B cells, in particular, how AFP impacts on their capacity to produce IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies have proposed that AFP is able to regulate other immune cells. Tumor-derived AFP causes suppression of T lymphocyte responses (44). Here, we intended to understand the effect of fetus-derived AFP on B cells, in particular, how AFP impacts on their capacity to produce IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…We have observed that uptake of AFP causes morphologic change in monocyte-derived DC (DC) and impairs their differentiation [3]. The effects of tumor-derived AFP (tAFP) are more potent than those of cord blood-derived “normal” AFP (nAFP).…”
Section: Introductionmentioning
confidence: 99%
“…In HCC patients exhibiting high levels of serum tAFP, we have observed a lower ratio of myeloid-to-plasmacytoid circulating DC compared to patients with low serum AFP levels and healthy donors [42]. To test the possible effect of nAFP or tAFP on DC differentiation, peripheral blood monocytes were cultured in vitro in the presence of nAFP or HCC-derived tAFP, and DC phenotype and function was assessed [42].…”
Section: Discussionmentioning
confidence: 99%
“…To test the possible effect of nAFP or tAFP on DC differentiation, peripheral blood monocytes were cultured in vitro in the presence of nAFP or HCC-derived tAFP, and DC phenotype and function was assessed [42]. Although the nAFP and tAFP isoforms only differ at one glycosylation site, low levels of tAFP significantly inhibited DC differentiation while nAFP had a more modest impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation